Differential gene expression profile in the small intestines of mice lacking pacemaker interstitial cells of Cajal - Ward Sean M; Caldas Carlos; Ponder Bruce AJ; Takayama Ichiro; Daigo Yataro; Sanders Kenton M; Fujino Masayuki A (BMC Gastroenterology, 2003)
Abstract Background We previously identified eight known and novel genes differentially expressed in the small intestines of wild type and W/WV mice, which have greatly reduced populations of the interstitial cells of Cajal, that are responsible for the generation of electrical slow waves, by using a differential gene display method. Methods By using the same method we isolated additional candidate genes that were specifically down- or up-regulated in W/WV mice. Novel transcripts were designated as DDWMEST. Results We isolated seven candidates that were specifically down- or up-regulated in W/WV mice. Two novel transcripts, DDWMEST 1 and -91 were increased in both fed and fasted W/WV mice. Expression of another five genes was suppressed in W/WV mice: ARG2 (Arginase II), ONZIN (encoding leukemia inhibitory factor regulated protein), and three novel transcripts: DDWMEST62, -84, and -100. Together with the previous report, we identified fifteen differentially expressed genes in total in the small intestines of W/WV mice. Eight of these genes were reduced in the jejunums of W/WV mice compared to age matched wild type mice, whereas the other seven genes showed an increase in expression. Differential expression was the same in fasted and fed animals, suggesting that the differences were independent of the dietetic state of the animal. Conclusions Several known and novel genes are differentially expressed in the small intestines of W/WV mice. Differential gene comparison might contribute to our understanding of motility disorders associated with the loss of the interstitial cells of Cajal.